The health system and access to treatment in patients with cervical cancer in Mexico - Arango-Bravo, Eder A.; Cetina-Pérez, Lucely del Carmen; Galicia-Carmona, Tatiana; Castro-Eguiluz, Denisse; Gallardo-Rincón, Dolores; Cruz-Bautista, Ivette; Duenas-Gonzalez, Alfonso (Frontiers in Oncology, 2022)
Cervical cancer (CC) is tightly related to a low Human Development Index. Mexico is an upper-middle-income country with 126 million inhabitants, and its public health system aims to provide universal health coverage. Currently, employment-based social insurance covers approximately 60% of the population, and the scope of the remaining 40% is on course via the “IMSS-Bienestar” Institute. However, the annual government spending on health remains at 3% of the Gross Domestic Product, which is well below the 6% recommended by the Organization for Economic Cooperation and Development. CC is the second in incidence and mortality among women. Regarding primary prevention with the Human Papilloma Virus-vaccine, the current coverage for girls aged 9 to 14 years is only around 7%. Among secondary prevention with screening, the program is yet to cover the total number of women at risk; nevertheless, the age-standardized CC mortality rate has decreased from 12 per 100,000 women in 1979 to 5.7 per 100,000 women in 2020 due in part to increased screening coverage. Still, around two-thirds of patients present with locally advanced disease at diagnosis. Data from our country demonstrate that even socially disadvantaged CC patients achieve “standard” survival outcomes if treatment is granted. Nevertheless, there is a shortage in almost every aspect regarding CC treatment, including oncologists, chemotherapy units, medical physicists, radiation technicians, and both teletherapy and brachytherapy facilities. In conclusion, advances in the public health system in Mexico are urgently required to achieve CC control and reduce the mortality from this neoplasia that mainly targets socially disadvantaged women.